Child Care Use among Adolescent Mothers Enrolled in a Massachusetts Home Visiting Program - Hoysgaard, LunYan. (2017)
Abstract: This thesis examines how young parents arrange child care for infants and toddlers, using a sample of adolescent mothers participating in an evaluation of a statewide home visiting program, Healthy Families Massachusetts (HFM). It describes the range of child care decisions mothers make, and determines the extent to which selected characteristics are related to these choices. The literature suggests that child care choices and policy for these mothers are constrained by the same factors that influence all mothers' care choices: quality, access, and affordability. As expected, findings from this thesis suggest that several maternal characteristics, including education/employment and voucher use, are associated with child care choices. While participation in home visiting can emphasize the importance of child care and direct choices to some degree, this association was not observed in this study; insofar as HFM does not explicitly work to optimize child care choice, so this finding was expected. It is recommended that home visitors inform clients about quality care and support them in accessing care, given their role in helping young parents. Despite the lack of association between teens' self-reported financial resources and care use or type of care in this study, the long wait list for vouchers and high rates of relative care use indicate cost may be a hurdle for parents in using more group care. This thesis is informative in guiding future work that combines the efforts of home visiting and child care to improve the outcomes of children of adolescent parents.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Francine Jacobs.; Committee: Barbara Parmenter, and Rebecca Fauth.; Keyword: Public policy.